The Špica pile-dwelling site – analyses of archaeological wood - Elena Leghissa; Mojca Jančar; Maks Merela; Luka Krže; Benjamin Štular; Anton Velušček; Katarina Čufar (Les)
We present the investigation of wood discovered during the 2009/2010 archaeological excavations at the prehistoric pile-dwelling settlement of Špica in Ljubljansko barje, Slovenia. The results include data on wood identification, dendrochronological dating and the spatial distribution of the piles. We focussed on smaller sections of the site and dated oak and ash piles with the reference chronologies of the pile-dwelling settlements of Založnica and Parte spanning the period 2659 – 2366 BC. Based on the established dates of tree felling, we identified several construction activities between 2522 and 2406 BC. Due to the time span of the available reference chronologies, it was not possible to date the wood eventually felled before or after 2659 – 2366 BC. The analyses of the wood together with earlier analyses of archaeological artefacts allow a better understanding of the chronological framework of the Špica site, although this study could not exploit the entire research potential of the excavated archaeological wood.